Development of special service tools tracker kingpin hino series 300 to increase technician work efficiency - Adhe Satria; Yoga Guntur Sampurno (Journal of Automotive and Mechanical Applied Technology, 2025)
This study focused on the design, development, and evaluation of a Special Service Tool (SST) created explicitly for maintaining kingpin components in Hino Series 300 trucks. The research focused on the challenges and safety issues encountered by technicians stemming from the lack of specialized tools for kingpin removal. This often led to extended service times, variable repair quality, and a heightened risk of damaging components. To address these challenges, the research employed the ADDIE development model, which comprises five stages: Analysis, Design, Development, Implementation, and Evaluation. In the design phase, 3D modeling was performed using SolidWorks, and Finite Element Analysis (FEA) was conducted to verify the tool's structural integrity under various load scenarios, reaching up to 19,613 N. The SST was made from ASTM A36 steel, recognized for its mechanical strength and ease of manufacturing. The simulation results demonstrated that the structure stayed within safe limits for both stress and deformation, achieving a minimum safety factor of 1.1. The implementation took place at PT. MPM Hino Yogyakarta, where field testing showed a significant enhancement in technician efficiency. The SST cut down kingpin maintenance time from 360 minutes to only 42.08 minutes, achieving an impressive 88.3% reduction in time spent. Testing for effectiveness, based on feedback from technicians and supervisors, revealed a high level of user satisfaction, particularly in terms of safety, usability, and ergonomic design. The SST tracker kingpin provides a dependable, effective, and secure option for maintaining commercial vehicles. The successful application of it at a Hino service center highlights its practical benefits and the potential for wider implementation throughout the automotive maintenance sector. Additional improvements could involve ergonomic adjustments and the ability to accommodate various truck models, thereby facilitating broader use.